The Influence of Price, Product Quality, Customer Rating, and Online Customer Review on Consumer Trust in TikTok Shop Users in Bali Province - Sumariani, Ni Putu Ayu (Klabat Journal of Management, 2025)
This study aims to analyze the influence of price, product quality, customer rating, and online customer reviews on consumer trust among TikTok Shop users in Bali Province. TikTok Shop, as a social commerce platform, has experienced rapid growth and is widely used by various segments of society. Due to the large number of users, the quota sampling technique was employed to determine respondents proportionally. Each variable was allocated a quota of 20 respondents, resulting in a total sample size of 100 respondents based on five research variables. This research applies a quantitative approach by distributing online questionnaires to active TikTok Shop users in Bali. The collected data were analyzed using SPSS version 24, and multiple linear regression analysis was conducted to examine the effect of each independent variable on consumer trust. The results show that price, product quality, customer rating, and online customer review each have a positive and significant effect on consumer trust, both partially and simultaneously. These findings suggest that consumer trust is influenced not only by pricing and product quality but also by the experiences and evaluations shared by other users on the platform.